Evaluation of Social Minimum Services: A Case Study in Gorontalo Province, Indonesia - Soedjono Adam, Erfirmansyah; Tahir, Arifin; Abdussamad, Zuchri; Aneta, Yanti (Iapa Proceedings Conference, 2024)
This study aims to evaluate the Minimum Service Standard policy in the social sector in Gorontalo Province. The implementation of Minimum Service Standards in the social sector in Gorontalo Province has still not reached the expected optimal target. Some of the main factors that affect the implementation of the Minimum Service Standards in this area include budget limitations, lack of adequate service facilities, and weak coordination between related institutions. This study uses a retroactive evaluation approach to assess the extent to which the implementation of this policy is running, focusing on the potential, policy, and impact of the implementation of the Minimum Service Standards in the field. Based on the results of the analysis, it was found that the achievement of the Minimum Service Standards indicator in several categories is still low, especially in services for people with disabilities, abandoned children, and the elderly in social institutions. This shortage is caused by limited regional budget allocation, lack of professionals, and the absence of more detailed derivative regulations to support policy implementation at the operational level. In addition, the synergy between institutions in the implementation of social programs is also not optimal, resulting in the low quality of services provided to the community. The implications of these findings show that there is a need for the preparation of more specific derivative regulations, institutional capacity building, and more adequate budget allocation to support the implementation of Minimum Service Standards in Gorontalo Province. With improvements in these three aspects, it is hoped that the quality of social services in Gorontalo Province can meet national standards and have a more positive impact on the welfare of people in need. This research makes an important contribution to more effective policy-making in efforts to optimize social services in accordance with the Minimum Service Standards.